Sociological Study of the Impact of Community Education in Border Area (Sociological Study Of Education in Sota Merauke) - Betaubun, Restu Monika Nia; Suratni, Suratni; Kalalo, Julianto Jover Jotam; Marpaung, Dewi Natalia (Musamus Journal of Public Administration, 2024)
The meaning of education can be seen from several different perspectives, from a psychological perspective or a sociological perspective. There are many understandings and definitions that discuss education, depending on how education is viewed. However, the essence of the meaning of the concept of education leads to one goal, namely an effort that is used as a process in fostering a person or society in general so that it can bridge the steps in living life so that they can achieve the life that everyone dreams of, namely enjoying a life that is based on knowledge and a prosperous life, all needs are met with the emergence of creative and innovative ideas that can only be obtained through the process of getting an education. The background to the development of education in the interior of Papua is still an important note for the government in realizing the fifth principle related to the implementation of social justice for all Indonesian people. Education on the border also functions and plays a role as the vanguard of preserving and guarding culture. Local and national traditions and customs must be maintained amidst the erosion of national identity. This study was conducted with the aim of describing and analyzing the picture of border area communities on how important education is and the factors that influence the low level of education in border areas. This study uses a quantitative approach with a descriptive method. The data collection method is carried out by collecting primary and secondary data. Primary data is obtained through distributing questionnaires and interviews. Secondary data is obtained through literature studies and documentation by studying the results of studies and relevant documents. The population in this study is the entire border area community with the sample taken being the community of Sota-Merauke District. This study is expected to produce a study on the importance of education for border area communities, especially in Sota-Merauke District.